2008
DOI: 10.1002/hep.22437
|View full text |Cite
|
Sign up to set email alerts
|

The epidermal growth factor receptor ligand amphiregulin participates in the development of mouse liver fibrosis†

Abstract: The hepatic wound-healing response to chronic noxious stimuli may lead to liver fibrosis, a condition characterized by excessive deposition of extracellular matrix. Fibrogenic cells, including hepatic stellate cells and myofibroblasts, are activated in response to a variety of cytokines, growth factors, and inflammatory mediators. The involvement of members of the epidermal growth factor family in this process has been suggested. Amphiregulin (AR) is an epidermal growth factor receptor (EGFR) ligand specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 46 publications
5
119
0
3
Order By: Relevance
“…2 It is also known that amphiregulin amplifies the HSC response through increased production of CTGF and TIMP-1. 39 Thus, the inhibition of amphiregulin expression by melatonin in CCl 4 -treated mice supports the suggestion that suppression of the amphiregulin signaling system could be a new target in the prevention of liver fibrosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…2 It is also known that amphiregulin amplifies the HSC response through increased production of CTGF and TIMP-1. 39 Thus, the inhibition of amphiregulin expression by melatonin in CCl 4 -treated mice supports the suggestion that suppression of the amphiregulin signaling system could be a new target in the prevention of liver fibrosis.…”
Section: Discussionsupporting
confidence: 59%
“…38 The expression of amphiregulin increases markedly in liver injury induced by CCl 4 , 39 and amphiregulin deficient-mice develop significantly less collagen accumulation. 40 We have previously reported that suppression of amphiregulin signals contributes to the protective effects of quercetin in cirrhotic rats with common bile duct ligation, 7 and in mice fed a methionine-choline-deficient diet.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have been undertaken to define the specific role of AR in the pathogenesis of tissue fibrosis, including pulmonary fibrosis, the available results have been conflicting to date. In an animal model of liver fibrosis, AR expression is significantly induced, and the absence of AR markedly reduced ␣-SMA expression and collagen deposition in the liver, implicating AR contribution in the development or the progression of liver fibrosis (42). In support of this notion, the use of gefitinib, a EGFR blocker, significantly inhibits bleomycin-induced pulmonary fibrosis (22).…”
Section: Discussionmentioning
confidence: 96%
“…[97][98][99][100][101][102] EGFR is expressed in both the parenchymal and nonparenchymal liver cells, and several studies have reported that amphiregulin enhances liver fibrosis through its mitogenic effect on HSCs. 102,103 These effects, protecting hepatocytes as well as profibrotic HSCs, could account for the fact that ADAM17 hepatocyte-deficient mice do not develop exaggerated fibrosis after intoxication with CCl 4 (our observation, unpublished). Similarly, despite certain dysregulations, no major liver regeneration phenotypes were observed in mice with ADAM17 deficiency in either hepatocytes or Kupffer cells.…”
Section: Regulator Of Growth Factor Signaling In the Livermentioning
confidence: 99%